Partnership Model Between MSMEs and Industrial Companies in West Java to Improve MSME Performance Through Digital Competency, Sustainable Value Creation, Community Involvement and Development - Merliana, Karlina; Andrawina, Luciana; Sriwana, Iphov Kumala (eProceedings of Engineering, 2025)
Micro, Small, and Medium Enterprises orMSMEs are crucial to Indonesia's economy, contributing over50% to the national GDP, absorbing 97% of the workforce, anddemonstrating significant potential for growth throughpartnership programs, digital transformation, and sustainablevalue creation, despite challenges such as fluctuating economicgrowth and low levels of collaboration with large enterprises.This study aims to design an effective partnership programbetween industrial companies and MSMEs in West Java.Focusing on MSMEs, this study examines how the variables ofdigital competence, sustainable value creation and communityinvolvement and development are able to influence partnershipprograms which ultimately have an impact on MSMEsperformance. The population in this study were MSMEsbusiness actors in West Java who had collaborated withindustrial companies. While the sampling technique usedpurposive sampling where the sample used in this study was 97MSMEs business actors. Data analysis used Smart PLS 4 basedPartial Least Square. Based on the results of the direct influenceanalysis, it shows that Digital Competence has a significanteffect on community involvement and development; communityinvolvement and development have a significant effect onpartnership programs; sustainable value creation has asignificant effect on partnership programs; and PartnershipPrograms have a significant effect on SME Performance. Whilethe results of the indirect influence analysis show that digitalcompetence has a significant effect on community involvementand development and partnership programs.